The COVID 19 novel coronavirus pandemic 2020: seaweeds to the rescue? Why does substantial, supporting research about the antiviral properties of seaweed polysaccharides seem to go unrecognized by the pharmaceutical community in these desperate times? - Pereira, Leonel; Critchley, Alan T. (Journal of applied phycology, 2020)
Presently, there is lack of a vaccine that would lead to immunization against the virus COVID-19, but here are some of the characteristics that various seaweeds have and which may provide a glimpse into potential solutions of this global health problem in the near future and possibly forearm us for any future such pandemics. Many species of marine algae contain significant quantities of complex structural sulphated polysaccharides that have been shown to inhibit the replication of enveloped viruses. Other compounds, both of red algae (e.g., the lectin griffithsin and the phycocolloid carrageenan), and other sulphated polysaccharides extracted from green algae (i.e., ulvans) and brown algae (i.e., fucoidans) could be potential antiviral therapeutic agents against SARS-CoV-2.